2019 IEEE International Conference on Systems, Man and Cybernetics (SMC) 2019
DOI: 10.1109/smc.2019.8914672
|View full text |Cite
|
Sign up to set email alerts
|

How Can Social Networks Design Trigger Fear of Missing Out?

Abstract: Social Network Sites (SNSs) are meant to facilitate interaction between people. The design of SNSs employs persuasive techniques with the aim of enhancing the user experience but also increasing interaction and user retention. Examples include the personalisation of content, temporarily available feeds, and notification and alert features. Socialness is now being embedded in new paradigms such as the Internet of Things and cyber-physical systems where devices can link people to each other and increase relatedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
2
31
1
Order By: Relevance
“…Previous research [ 2 , 18 , 19 ] has identified five primary contexts of use where FoMO occurs, the fears associated with them and the potential technical countermeasures. The findings are summarised in Table 1 .…”
Section: Fomo Reduction Methods (Fomo-r): Theoretical Underpinningsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research [ 2 , 18 , 19 ] has identified five primary contexts of use where FoMO occurs, the fears associated with them and the potential technical countermeasures. The findings are summarised in Table 1 .…”
Section: Fomo Reduction Methods (Fomo-r): Theoretical Underpinningsmentioning
confidence: 99%
“…These studies developed five primary contexts of use in which FoMO occurs and the specific fears in each context [ 2 ]. The same authors explored features of social media that could facilitate FoMO and, in addition, the existing and future social media features that alleviate FoMO [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Setting others’ expectations can be achieved by declaring some information regarding user’s availability, or the tasks that users are currently performing, and making those situations transparent to peers. Confirming the availability time can also reduce the fear of missing out (FoMO) where users fear being ignored or excluded [ 7 , 20 ]. Being transparent can inspire and create trust between users and provide an excuse to avoid interacting with others during the unavailability time.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Therefore, the distracting notification can be considered an external factor that could invoke and facilitate procrastination. Moreover, the design features of social networking sites (SNS) could facilitate procrastination in numerous cases such as users who instantly reply to messages to develop a positive self-image or because of the fear of missing out [ 7 , 8 ]. It has been suggested that procrastination is a trait that is determined by underlying personality factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%